Design and development of an automated launch system for sewer inspection robot - Khoo, Yi Quan (Nanyang Technological University, 2020)
Securing Singapore’s self-sustainability in clean water, the government has invested a considerable amount into constructing used water tunnels throughout our island. The sewer networks consist of three different types of tunnels: Trunk Sewer Tunnels, Link Sewer Tunnels and the Deep Tunnels Sewer. The largest diameter sewer tunnel in Singapore, the Deep Tunnel Sewer System (DTSS) has a diameter of 6.5m, consist of up to 80km long and are constructed up to 55m deep. While tunnels are generally not the most conducive environments for humans, they are dark and may contain poisonous gases in addition to posing a risk of explosion. NTU has developed a family of sewer inspection robots for the three types of sewer tunnels in Singapore. Although the traditional way of manual inspection and maintenance of the used water tunnel now can be done with the more capable sewer inspection robot, replacing the slow and inefficient method done with humans. However, the robotic platform still requires human intervention for deployment and recovery operations. Among the researches, none of the deployment cage designs could be used directly in Singapore’s used water tunnel system due to manhole entrance in Singapore being as small as 0.6m in diameter and the presence of intermediate platform within the access shaft in some of the tunnel systems. Therefore, this project focuses on design of a deployment system focusing on the link sewer tunnels, with manhole opening of 0.7m in diameter and with the presence of intermediate platform and railings within the access shaft.